Mulberry Twig Alkaloids Improved the Progression of Metabolic-Associated Fatty Liver Disease in High-Fat Diet-Induced Obese Mice by Regulating the PGC1α/PPARα and KEAP1/NRF2 Pathways - Mengqing Zhang; Chengcheng Guo; Zonglin Li; Xiaoling Cai; Xin Wen; Fang Lv; Chu Lin; Linong Ji (MDPI AG, 2024)
Background/Objectives: Metabolic-associated fatty liver disease (MAFLD) is one of the most common liver disorders associated with obesity and metabolic syndrome, and poses a significant global health burden with limited effective treatments. The aim of this study was to assess the protective effects of mulberry twig alkaloids (SZ-A) on MAFLD and to further investigate the underlying mechanisms including the specific targets or pathways. Methods: Diet-induced obesity (DIO) and normal mouse models were established by feeding C57Bl/6J mice with a high-fat diet (HFD) or common diet for 12 weeks. SZ-A, dapagliflozin, and placebo were administered to corresponding mouse groups for 8 weeks. Data of fasting blood glucose, glucose tolerance, insulin tolerance, and the body weight of mice were collected at the baseline and termination of the experiment. Serum liver enzymes and lipids were measured by ELISA. Western blotting, qPCR, and pathological section staining were implemented to evaluate the degrees of liver steatosis, fibrosis, and oxidative stress in mice. Results: In DIO mouse models, high-dose SZ-A (800 mg/kg/d) treatment significantly inhibited HFD-induced weight gain, improved insulin tolerance, and reduced serum alanine aminotransferase, total cholesterol, and triglyceride levels compared with placebo. In DIO mice, SZ-A could alleviate the pathological changes of hepatic steatosis and fibrosis compared with placebo. Lipid catabolism and antioxidant stress-related proteins were significantly increased in the livers of the high-dose SZ-A group (p < 0.05). Inhibition of PGC1α could inhibit the function of SZ-A to enhance lipid metabolism in hepatocytes. PGC1α might interact with NRF2 to exert MAFLD-remedying effects. Conclusions: By regulating the expression of PGC1α and its interacting KEAP1/NRF2 pathway in mouse liver cells, SZ-A played important roles in regulating lipid metabolism, inhibiting oxidative stress, and postponing liver fibrosis in mice with MAFLD.